Dynamic crack branching and curving in brittle polymers. (1st December 2016) - Lee, Jooeun; Hong, Jung-Wuk
Abstract: This paper presents peridynamics simulation on crack branching and curving in a pre-existing center-notched brittle polymer. Fracturing patterns in brittle polymer under a biaxial tensile loading condition are compared with experimental observations for validation. Then, several numerical examples are conducted in order to investigate crack initiation and propagation of the pre-existing center notch under the effect of different loading ratios. Further to this, the crack development sequences of branching and curving are in detail discussed, and their underlying causes are identified through various perspectives including crack curving and branching angles, elastic strain energy, and branching damage patterns. The numerical results reasonably reflect the physical observations. This paper both complements the test results and provides insightful information for the prediction of crack branching and curving in brittle polymers.